2010
DOI: 10.1039/c0nr00304b
|View full text |Cite
|
Sign up to set email alerts
|

Signal transmission, conversion and multiplication by polar molecules confined in nanochannels

Abstract: The mechanism of signal transmission, conversion and multiplication at molecular level has been of great interest lately, due to its wide applications in nanoscience and nanotechnology. The interferences between authentic signals and thermal noises at the nanoscale make it difficult for molecular signal transduction. Here we review some of our recent progress on the signal transduction mediated by water and other polar molecules confined in nanochannels, such as Y-shaped carbon nanotubes. We also explore possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 66 publications
1
34
0
Order By: Relevance
“…15(b) and (e)], which was much more stable than single strand in bulk water. Our recently theoretical investigation has shown that the hydrophobic effect plays a significant role in protein self-assembly in water, in which the "dewetting transition" can be induced by the hydrophobic interaction between two strands in both amyloid-β peptides (KLVFFAE) and hIAPP [22][23][24][25][26][27] peptides (NFGAIL) [107,108]. Our simulations confirm that beta-strand conformation can be stabilized in hydrophobic environment, which could further promote the formation of protofilaments and form amyloid fibrils.…”
Section: Conformational Change Of Small Peptides In Carbon Nanotubessupporting
confidence: 50%
See 3 more Smart Citations
“…15(b) and (e)], which was much more stable than single strand in bulk water. Our recently theoretical investigation has shown that the hydrophobic effect plays a significant role in protein self-assembly in water, in which the "dewetting transition" can be induced by the hydrophobic interaction between two strands in both amyloid-β peptides (KLVFFAE) and hIAPP [22][23][24][25][26][27] peptides (NFGAIL) [107,108]. Our simulations confirm that beta-strand conformation can be stabilized in hydrophobic environment, which could further promote the formation of protofilaments and form amyloid fibrils.…”
Section: Conformational Change Of Small Peptides In Carbon Nanotubessupporting
confidence: 50%
“…The structure of this chapter will be organized as following. First, we show that water molecules confined within a Y-shaped CNT can realize the molecular signal conversion and multiplication, due to the surprisingly strong dipole-induced orientation ordering of confined water wires [25]. Second, we find a striking phenomen that urea can induce the drying of CNTs and result in single-file urea wires.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…[4][5][6][7][8]. Molecular dynamics (MD) simulations have explored the effects of an electric field on nanochannel transportation characteristics, where an electric field can be achieved by assigning charges near a nanochannel [9][10][11][12][13][14][15], adding ions to the water phases on both sides of a nanotube [16][17][18], or directly using MD software such as NAMD [8,19,20], GROMACS, etc. [21][22][23].…”
Section: Introductionmentioning
confidence: 99%